Two Zn(II) coordination polymers constructed from sulfate and isomeric viologen-carboxylate ligands: Crystal structures, photochromism and ammonia vapochromism. (November 2021) - Li, Zhao-Hao; Xue, Li-Ping; Wu, Yue; Wang, Qing; Zhao, Bang-Tun
Abstract: Nowadays, the exploration of chromic materials has been highly desirable owing to their appealing applications. In this work, two Zn(II) coordination polymers constructed from sulfate and isomeric viologen-carboxylate ligands, formulated as [Zn(L1) (SO4 )](H2 O)2 n (1), [Zn(L2) (SO4 ) (H2 O)2 ](H2 O)3 n (2) (L1 = N -(3-carboxy(pyridin-2-yl))-4, 4′-bipyridinium, L2 = N -(4-carboxypyridin-3-yl)-4, 4′-bipyridinium) have been synthesized and characterized. Single crystal X-ray analyses reveal that 1 features a 2D layer structure and 2 discloses a 1D chain structure. As expected, 1 and 2 exhibit sensitive photochromic properties under xenon light irradiation due to the formation of photoinduced radicals. Moreover, 1 displays a color change detectable by the eye when exposed to ammonia vapor. These results provide some useful guidance to explore new chromic crystalline materials. Graphical abstract: Image 1 Highlights: ► Two Zn(II) coordination polymers constructed from two isomeric viologen-carboxylate ligands and sulfate have been synthesized. ► Compounds exhibit sensitive photochromic behaviors. ► One compound displays ammonia vapochromic behavior.